Production of Biopolymer Polyhydroxyalkanoates (PHA) by Extreme Halophilic Marine Archaea Haloferax mediterranei in Medium with Varying Phosphorus Concentration - Melanie, Susiana; Winterburn, James B.; Devianto, Hary (Journal of Engineering and Technological Sciences, 2018)
The development of plastics production from biodegradable resources such as polyhydroxyalkanoates (PHAs) is important due to the increasing demand for plastics. PHAs occur as intracellular solid materials produced by microorganisms as a result of an excess of carbon source and a limitation of nutrients. Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) or PHBV, as one of the PHAs, is a combination of two homopolymers, namely poly-3-hydroxybutyrates (PHB) and poly-3-hydroxyvalerates (PHV). This study aimed to investigate the effect of the phosphorus concentration on the production of PHAs by Haloferax mediterranei. It is possible that phosphorus deficiency may affect the length of the HV chains in the copolymer structure and thus influence the copolymer properties. The experiment was done in triplicate at laboratory scale by culturing H. mediterranei in medium with phosphorus limitation using various phosphorus concentrations. During cultivation, the optical density, phosphorus concentration, pH, and dry cell weight were observed. The PHBV product was collected and analyzed using gas chromatography. The result shows that medium with a phosphorus concentration of 0.5 g/L produced higher PHAs than the other phosphorus concentrations. The accumulated PHA was 0.95 g/L with 15.6% of dry biomass and yield YPHA/S of 0.1 g/g.